Protocol of a first-in-human clinical trial to evaluate the safety, tolerability, and preliminary efficacy of the bispecific CD276xCD3 antibody CC-3 in patients with colorectal cancer (CoRe_CC-3) - Jung, Susanne Claudia; Schlenk, Richard Friedrich; Hackenbruch, Christopher; Roldan Pinzon, Sandra S. L.; Bitzer, Michael; Pflügler, Martin; Walz, Juliane S.; Jung, Gundram; Heitmann, Jonas S.; Salih, Helmut R. (Frontiers in oncology, 2024)
Introduction Colorectal cancer (CRC) is the third most common cancer worldwide in men and women. In the metastasized stage, treatment options and prognosis are limited. To address the high medical need of this patient population, we generated a CD276xCD3 bispecific antibody termed CC-3. CD276 is expressed on CRC cells and on tumor vessels, thereby allowing for a “dual” anticancer effect. Methods and analysis This first-in-human clinical study is planned as a prospective multicenter trial, enrolling patients with metastatic CRC after three lines of therapy. During the dose-escalation part, initially, an accelerated titration design with single-patient cohorts is employed. Here, each patient will receive a fixed dose level (starting with 50 µg for the first patient); however, between patients, dose level may be increased by up to 100%, depending on the decision of a safety review committee. Upon occurrence of any adverse events (AEs) grade ≥2, dose-limiting toxicity (DLT), or reaching a dose level of ≥800 µg, the escalation will switch to a standard 3 + 3 dose design. After maximum tolerated dose (MTD) has been determined, defined as no more than one of the six patients experiencing DLT, an additional 14 patients receive CC-3 at the MTD level in the dose-expansion phase. Primary endpoints are incidence and severity of AEs, as well as the best objective response to the treatment according to response evaluation criteria in solid tumors (RECIST) 1.1. Secondary endpoints include overall safety, efficacy, survival, quality of life, and pharmacokinetic investigations. Ethics and dissemination The CD276xCD3 study was approved by the Ethics Committee of the Medical Faculty of the Heinrich Heine University Düsseldorf and the Paul-Ehrlich-Institut (P00702). Clinical trial results will be published in peer-reviewed journals. Trial registration numbers: ClinicalTrials.cov Registry (NCT05999396) and EU ClinicalTrials Registry (EU trial number 2022-503084-15-00).
Gesehen am 15.01.2025
Online veröffentlicht: 12. Februar 2024